God's country [videorecording (DVD)] - Higgins, Julian, 1985-; Ogbonna, Shaye; Newton, Thandiwe, 1972-; Bobb, Jeremy; Jarsky, Joris, 1974-; Lennox, Kai; White, Jefferson (Actor); Beatty, Tanaya; Burke, James Lee, 1936- (IFC Films, 2023)
When a college professor in the remote mountains of the American West confronts two hunters she catches trespassing on her property, she's drawn into an escalating battle of wills with catastrophic consequences.